Financial Technology with QRIS Payment System for Entrepreneurship Locker - Victorio Almers Chrisetya Putra; FX Hendra Prasetya; Bernardinus Harnadi; Albertus Dwiyoga Widiantoro (Soegijapranata Catholic University, 2023)
The Covid-19 pandemic has an impact not only on health but also on human activities, one of which is economic transactions. A number of policies related to health protocols have caused limitations for the community in transacting with each other. In relation to economic transactions, entrepreneurial transactions on campus have stopped due to policies related to the pandemic. To answer this problem, an invention called